Dialektika Influencer pada Ekosistem Bisnis Digital: Analisis Multidimensi Komodifikasi di Indonesia - Yudhi Hertanto (LP3M Universitas Putra Bangsa, 2026)
The rapid development of Indonesia’s digital business and social commerce ecosystem has positioned influencers as central actors in contemporary marketing dynamics. However, the shift from authentic personal recommendations to large-scale commercialization has created multidimensional complexities that contribute to legal compliance issues, social erosion, and ethical dilemmas. This study aims to provide an in-depth analysis of the role and position of influencers in Indonesia’s digital business ecosystem through three analytical perspectives: juridical, sociological, and philosophical. This study employs a qualitative descriptive-analytical method by integrating socio-legal and doctrinal research approaches. The analysis is based on a synthesis of reputable scholarly literature, statutory regulations, and data on digital industry performance. The findings reveal that, from a juridical perspective, the legal status of influencers remains ambiguous, particularly regarding accountability for misleading endorsements under the Consumer Protection Law and the Electronic Information and Transactions Law. Furthermore, the self-regulatory framework established by the Indonesian Advertising Code remains inadequate in addressing hidden advertising practices. From a sociological perspective, the exploitation of parasocial relationships and the commodification of social capital have contributed to increased digital sales conversions. Nevertheless, these practices have simultaneously led to the erosion of public trust and the emergence of communal sanctions manifested through cancel culture. From a philosophical perspective, influencers reflect an ontological condition of hyperreality and simulacra, an epistemological shift toward affective truth in the post-truth era, and axiological alienation resulting from self-commodification. This study recommends the introduction of specific regulations governing mandatory sponsorship disclosure, the revision of legal protections for digital consumers, and the establishment of continuous oversight mechanisms for digital platforms.